Was the Unseasonal Development of Post‐Sunset Equatorial Plasma Bubbles in Southeast Asia Driven by Quasi‐2‐Day Planetary Waves? - Guofeng Dai; Guozhu Li; Yuichi Otsuka; Lianhuan Hu; Wenjie Sun; Baiqi Ning; Donghe Zhang; Jiuhou Lei; Haiyong Xie; Xiukuan Zhao; Michi Nishioka; Septi Perwitasari; et al. (Journal of Geophysical Research Space Physics, 2025)
Abstract Previous studies suggest that the planetary waves in mesosphere and low thermosphere (MLT) could modulate the occurrence of equatorial plasma bubbles (EPBs) via altering post‐sunset F layer height. Using simultaneous observations by Global Navigation Satellite System receiver networks, two ionosondes separated by about 10° in longitude, high frequency and very high frequency radars, we investigated the day‐to‐day variations of post‐sunset F layer height and EPB occurrence in southeast Asia during the quasi‐2‐day planetary wave (QTDW) event in July 2023. The results showed that the post‐sunset F layer height over Bac Lieu (9.3°N, 105.7°E) and EPB occurrence had a quasi‐2‐day (QTD) variation. However, such a 2 day variation of F layer height was confined in a very limited longitude, that is contradictory to the planetary scale characteristics of QTDW. We suggest that the QTD variations of post‐sunset F layer height and EPB occurrence over the specific location were not necessarily due to the QTDW in MLT. The local seeding source, as characterized by satellite traces in ionosonde ionograms, could drive the small‐scale longitudinal structure of F layer height and play an important role in shaping the QTD variation of EPB. The results implicate that the connection between planetary waves and the EPB occurrence over a specific location should be interpreted carefully, even if the day‐to‐day variation of post‐sunset F layer height shows periodic behavior with planetary wave scale.
Keywords: Ionosphere and magnetosphere dynamics; Solar and Space Plasma Dynamics; Tropical and Extratropical Cyclones Research